CLINICAL SAFETY OF ORAL LICOMYCIN TREATMENT IN NILE TILAPIA (Oreochromis niloticus) - COSTA, C. C.; OLIVEIRA, S. L.; ARACATI, M. F.; RODRIGUES, L. F.; MONTASSIER, H. J.; BELO, M. A. A. (Ars Veterinaria, 2022)
Lincomycin is a broad-spectrum antimicrobial acting against Gram-positive bacteria, widely used in veterinary medicine. In fish, there are only limited in vitro data, thus requiring the design of effective therapeutic protocols for their use in aquatic organisms. In this context, the objective was to evaluate the clinical safety of lincomycin treatment, administered orally in tilapia, through hematological, biochemical and somatic index evaluation. A total of 136 tilapia (±100g) were randomly distributed in 17 tanks (100L of water, n=8) to constitute the following treatments: T0 (control group, not treated with lincomycin); T1, T2, T3 (treated with 10, 20 and 40mg/kg-1 of lincomycin b.w., respectively) and T4 physiological standard (reference values). Eight animals were sampled per treatment in 4 periods: 2, 4 and 8 days post-treatment (DPT), and a group that was treated for 8 days with the drug and then treated only with commercial feed until the 12th day (recovery period). Tilapia treated with lincomycin had no difference in the hematological and leukocyte evaluation, in the hepatic, renal and splenic somatic index. However, they presented a transient increase in the values of ALT, AST, cholesterol, triglycerides and creatinine, which returned to normal levels after the period of recovery (12DPT). Furthermore, an increase in total protein, albumin and globulin levels was observed in treated animals. It is concluded that although there were some transient changes during the experiment, lincomycin has a good clinical safety margin at doses of 10, 20 and 40mg/Kg-1 b.w. for Nile tilapia.